Draft Genome Sequence of Pantoea agglomerans JM1, a Strain Isolated from Soil Polluted by Industrial Production of Beta-Lactam Antibiotics That Exhibits Valacyclovir-Like Hydrolase Activity - Zahradník, Jiří (Genome Announc, 2017)
Strain Pantoea agglomerans JM1 was isolated from the soil of a microbiome that had been exposed to polluting pharmaceuticals. The bacterium exhibited enzymatic activities useful for the biotransformation of beta-lactams. The genome of the strain was assembled and described, and the gene encoding valacyclovir-like hydrolase was identified.